Internet-Based Corporate Dosclosire and Market Value: Evidence from Latin America (2010)
We examine the relationship between corporate disclosure using the internet and firm value, and evaluate the relatively understudied corporate use of the internet by firms listed in the seven largest stock markets of Latin America (Argentina, Brazil -Bovespa and No-vomercado- Colombia, Chile, Mexico and Peru). We construct an internet-based corporate disclosure index (ICDI) for each firm listed in the aforementioned stock markets (for a total of 1,318 firms) and find that that an increase of 1% in the ICDI results in an average increase of 0.62% in Tobin's Q. These findings are robust after considering the potential endogeneity of our regression variables and after performing a battery of other robustness checks. Our results are consistent with the theoretical model of La Porta, et al. (2002) that related good corporate governance to higher investor confidence. These findings are relevant not only for Latin America but also for other emerging markets and regions in the process of attempting to improve their corporate disclosure practices. Two direct insights to policy makers and practitioners follow from our analysis: firstly, managers in weak investor protection environments could differentiate their firms by voluntarily disclosing financial and corporate governance information through their corporate websites; and secondly, our internet-based measure of corporate disclosure gives investors a quantitative tool to better assess Latin American firms.